2021
DOI: 10.1101/2021.05.03.442473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Binocular Mirror-Symmetric Microsaccadic Sampling EnablesDrosophilaHyperacute 3D-Vision

Abstract: Neural mechanisms behind stereopsis, which requires simultaneous disparity inputs from two eyes, have remained mysterious. Here we show how ultrafast mirror-symmetric photomechanical contractions in the frontal forward-facing left and right eye photoreceptors give Drosophila super-resolution 3D-vision. By interlinking multiscale in vivo assays with multiscale simulations, we reveal how these photoreceptor microsaccades - by verging, diverging and narrowing the eyes' overlapping receptive fields - channel depth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 141 publications
(573 reference statements)
0
4
0
Order By: Relevance
“…However, our experiments show that this is only partially true. Even though fruit flies perceive the world in 3-D 17 , surprisingly enough, we found that they also perceive information from static 2-D images, and are able to extract information from them. This indicates that pictures of sexual intercourses are recognised as such, leading females to react to the picture in the same way as they would to a real copulation, as we found.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, our experiments show that this is only partially true. Even though fruit flies perceive the world in 3-D 17 , surprisingly enough, we found that they also perceive information from static 2-D images, and are able to extract information from them. This indicates that pictures of sexual intercourses are recognised as such, leading females to react to the picture in the same way as they would to a real copulation, as we found.…”
Section: Discussionmentioning
confidence: 62%
“…Here, we report on a study in the model organism Drosophila melanogaster, where artificial visual stimuli have been used for decades mostly in simple forms to study navigation 15,16 . However, all these approaches use the capacity of fruit flies to have a 3-D perception of their environment 17 . As we wanted to investigate whether they also use 2-D images as sources of information and whether they can extract information from them, we modified the protocol to study social learning in the context of mate choice, a form that usually is called mate copying.…”
mentioning
confidence: 99%
“…Similarly, the ability to configure ommatidial properties individually and with respect to eye surface shape enables new investigations into the benefits of asymmetric compound eyes such as those found in robber flies ( Wardill et al, 2017 ) and crabs ( Zeil et al, 1986 ). Furthermore, we see opportunities to model the recently reported microsaccadic sampling in fruit flies ( Juusola et al, 2017 ), as well as aid with similar vision-centric neurological studies ( Viollet, 2014 ; Wystrach et al, 2016 ; Kemppainen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…50 It is noteworthy that the compound eyes of dragonflies and Coenosia also show partial curvature specialization, and the structure of ommatidia and the shape of compound eyes are both important to collect meaningful visual information. Recently, a study on Drosophila hyperacute 3D vision has been presented, 51 which suggests a general dynamic stereoinformation sampling strategy that could potentially be combined with bionic gradient compound eyes to provide advanced machine vision in the future. Meanwhile, studies on optical synapses based on MoS 2 have been emerging with promising developments in image sensing, learning, and memory functions for artificial visual systems, 52−54 and these advanced technologies have the potential to be combined with gradient compound eyes to advance the research and applications of bionic compound eyes.…”
Section: Optical Properties Of the Gradient Compoundmentioning
confidence: 99%